Trifold Display Board 3D As An Effort To Improve Knowledge And Brushing Skills For Early Childhood - Ety Sofia Ramadhan; Adriana Hamsar (Jurnal Kesehatan Gigi, 2022)
Introduction: A common dental and oral health problem is dental caries. The results of Riskesdas (2018), showed that children aged 5 years had a dental caries experience rate (dmft) ≥ 6 of 67.3%. The target of the Indonesian Ministry of Health is caries-free by 2030. Efforts to prevent dental and oral diseases are carried out through promotional and preventive services, through dental health education with various methods and media that are fun, entertaining and attract attention, and can help and accelerate the process of understanding children's material susbstantion. Objective: Produce a media Trifold Display Board 3D bagi anak usia dini. Method: Quasi-experiment with pre-posttest design and statistical test used is wilcoxon test. Results: The results in the poster group of knowledge research results p value 0.275, for skills p value 0.096 both showed results p ˃ 0.05, In the Poster Media group the change in values existed but did not show significant results in influencing knowledge and skills. In the 3D Trifold Display Board group, the results showed that both had a p value of 0.000 (p 0.05). Conclusion: The development of a Trifold Display Board 3D media application and effectively improves the dental health maintenance behavior of public elementary school early childhood  so that it can be an alternative problem-solving in improving the dental health maintenance behavior of elementary school early childhood.